ANALISIS PENGENDALIAN PERSEDIAAN BAHAN BAKU DENGAN MENGGUNAKAN METODE STOCKHASTIC PADA CV ISMA GARMENT DI SUKOHARJO - Ainunrizqiani Ainunrizqiani; Yohanes Djoko Suseno; Sunarso Sunarso (Universitas Slamet Riyadi, 2020)
The purpose of this study was to analyze the efficiency of the supply of raw material needs carried out by CV Isma Garment Sukoharjo, so as to maintain the stability of production process. Research methods using case studies in CV Isma Garment Sukoharjo, data collection methods used: interviews, observation, and documentation. The data analysis technique used in this study is a stockhastic inventory control model using 90% and 95% service levels. The results showed that the control of raw material inventory implemented by CV Isma Garment Sukoharjo had not yet reached the level of efficiency of raw material inventory and cost efficiency. This is indicated by the results of calculations that have been carried out by the stockhastic method can produce efficiency of raw material inventory costs rather than the methods applied by the company.